Ich weiß, was du n\"achsten Sommer getan haben wirst: Predictive Policing in \"Osterreich - Adensamer, Angelika (2019)
Predictive policing is a data-based, predictive analytical technique used in law enforcement. In this paper, we give an overview of the current situation in Austria and discuss technical, sociopolitical and legal questions raised by the use of PP, such as the lack of awareness of discriminatory structures in society, the biases in data underlying PP and the lack of reflection on the basic premises and feedback mechanisms of PP. Violations of fundamental rights without cause are not allowed by the Austrian Code of Criminal Procedure (Strafprozeßordnung, StPO), the Security Police Act (Sicherheitspolizeigesetz, SPG) or the Act concerning Police Protection of the State (Polizeiliches Staatsschutzgesetz, PStSG); the principle of allowing police intervention only on the basis of concrete threats or suspicion must remain absolute. Considering the numerous problems (not least from the point of view of legal policy), we conclude that the use of PP should be eschewed and that resources and planning should instead be focussed on solving the social problems which actually cause crime.Comment: 14 pages, in Germa